Curcumin and cinnamon mitigates lead acetate-induced oxidative damage in the spleen of rats - Mahmoud Abdelghaffar Emam; Sameh Mohamed Farouk; Ahmed Aljazzar; Abeer A. Abdelhameed; Abeer A. Eldeeb; Fatma Abdel-monem Gad (Frontiers Media S.A., 2023)
Lead toxicity is a common occupational and environmental health hazard that exerts many toxic effects on animals and humans, including immunotoxicity. Curcumin (CUR) and cinnamon (CIN) are common medicinal herbs with immunostimulatory and antioxidant properties. Therefore, this study investigated the protective effect of curcumin and cinnamon against lead acetate (LA)-induced splenotoxicity in rats via hemato-biochemical, immunological, oxidative stress marker, CYP-2E1 expression, histological, and immunohistological evaluations. Four groups of seven rats each were used: the control group received corn oil as a vehicle; the lead acetate group received (100 mg/kg), the CUR + LA group received curcumin (400 mg/kg) plus lead acetate, and the CIN + LA group received cinnamon (200 mg/kg) plus lead acetate orally for 1 month. LA exposure induced macrocytic hypochromic anemia, leukocytosis, neutrophilia, monocytosis, and lymphopenia. Additionally, significant elevations in serum iron, ferritin levels, and transferrin saturation percentage with significant decline of total and unsaturated iron binding capacities (TIBC and UIBC), transferrin, and immunoglobulin G and M levels were recorded. In addition, lead acetate significantly upregulated splenic CYP-2E1 expression, that was evident by significant depletion of reduced glutathione (GSH) activity and elevation of malondihyde (MDA), nitric oxide (NO), and protein carbonyl (PC) concentrations in the spleen. Histologically, hyperplasia of lymphoid follicles, hemosiderin deposition, and disturbance of CD3 and CD68 immuno-expressions were evident in the spleen from the lead acetate group. However, curcumin and cinnamon administration restored the hemato-biochemical, immunological, and oxidative stress parameters as well as histological and immunohistological pictures toward normalcy. In conclusion, curcumin and cinnamon can partially ameliorate LA-induced oxidative damage in the spleen, possibly through their antioxidant, immunomodulatory, and gene-regulating activities.